1982
DOI: 10.1161/01.atv.2.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Arteriographic assessment of coronary atherosclerosis. Review of current methods, their limitations, and clinical applications.

Abstract: Coronary arteriography is presently the definitive procedure for characterizing the location and severity of coronary atherosclerosis; and despite certain reported limitations, we believe that the properly performed coronary arteriogram provides a true picture of the arterial lumen in life. Yet this widely-used clinical tool is currently limited by imprecise and, to a certain extent, inappropriate subjective methods of interpretation. More objective methods for analysis of the arteriographic information conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

1985
1985
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(31 citation statements)
references
References 61 publications
(38 reference statements)
1
25
0
3
Order By: Relevance
“…14 23 From these data, obtained in a clinical setting, a curvilinear relationship was found between the pressure drop across the stenosis and the minimal obstruction area as well as the percent cross-sectional area reduction. Both relationships are similar to those calculated on theoretical grounds by Brown et al 34 as well as to those experimentally derived from isolated human arteries35 or in canine experiments.3 Such a curvilinear relationship is expected from the general equation of fluid dynamics showing that a pressure drop across a stenosis is influenced mainly by viscous losses in the stenotic segment and separation losses at the exit of the stenosis. For a given level of flow, the single most important determinant of stenosis resistance is its minimal cross-sectional area, which appears as a second-order term in both viscous and separation loss equations.…”
Section: Discussionsupporting
confidence: 84%
“…14 23 From these data, obtained in a clinical setting, a curvilinear relationship was found between the pressure drop across the stenosis and the minimal obstruction area as well as the percent cross-sectional area reduction. Both relationships are similar to those calculated on theoretical grounds by Brown et al 34 as well as to those experimentally derived from isolated human arteries35 or in canine experiments.3 Such a curvilinear relationship is expected from the general equation of fluid dynamics showing that a pressure drop across a stenosis is influenced mainly by viscous losses in the stenotic segment and separation losses at the exit of the stenosis. For a given level of flow, the single most important determinant of stenosis resistance is its minimal cross-sectional area, which appears as a second-order term in both viscous and separation loss equations.…”
Section: Discussionsupporting
confidence: 84%
“…Angiograms were separated in time by an average of 2.5 years and analyzed by a computer-assisted method. 25 In the control group, 46% of subjects had lesion progression in at least one of nine proximal coronary segments. Progression was less frequent in subjects treated with colestipol-lovastatin (21%) and colestipolniacin (25%).…”
Section: Later Trialsmentioning
confidence: 99%
“…First, when multiple coronary lesions are present, the extent of concurrent myocardial damage influences symptoms and risk. 24 Second, equations predicting blood flow from lesion measurements in an unbranched vessel 25 oversimplify real coronary blood flow, which pulsates through highly branched vessels. 26 Last, certain plaques are likely sites for the local catastrophe of plaque fissuring with hematoma or thrombosis causing a rapid increase in size.…”
Section: Coronary Atherosclerosis Severity Versus Symptoms and Risk Omentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with nonobstructive CAD (percent stenosis less than 50%) were excluded from analysis because Fried and Pearson 19 have shown that such patients in fact have extensive disease and are difficult to categorize. In addition, Brown et al 20 have shown that assessment of coronary stenosis of 30-50% is highly variable and poorly reproducible among observers. Patients were considered to have normal coronary anatomy if no evidence of luminal irregularities was noted by the angiographer.…”
Section: Measurement Of Extent Of Coronary Atherosclerosismentioning
confidence: 99%